Mengurai Landasan Konseptual PAK Berbasis Multikultural dalam konteks Indonesia - I Made Suardana (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2020)
This study examines the implementation of Christian Religious Edu-cation in a multicultural society in the Indonesian context. The fundamental thing of concern is the weak adaptability of the multicultural context in PAK which is able to answer the demands of togetherness and equality amidst the various differences that exist as uniqueness and identity of self and group. A qualitative approach with descriptive research through analysis of descriptive-argumentative data used in this study is intended to bring researchers closer to the problems that exist in the field so that it fulfills the principles of adequacy and fulfillment of the required data. The results obtained are that PAK places its characteristics that are always dealing with multicultural contexts so that the context is not to be avoided but to be lived. Efforts to live up to the multicultural context in the realization of PAK place PAK attached to the foundation of Jesus' concern who loves everyone. Based on the research findings, it is highly recommended that the Indonesian context is always the answer to the achievement of the goals of PAK, an Indonesian culture that accepts, respects, and upholds the principle of living together. Abstrak Penelitian ini mengkaji implementasi Pendidikan Agama Kristen da-lam masyarakat multikultural konteks Indonesia. Hal mendasar yang menjadi keprihatinan adalah lemahnya kemampuan adaptasi konteks multikultural dalam PAK yang mampu menjawab tuntutan kebersamaan dan kesederajatan di tengah pelbagai perbedaan yang ada sebagai keunikan dan identitas diri dan kelompok. Pendekatan kualitatif dengan jenis penelitian deskriptif melalui analisis data deskriptif-argumentatif yang digunakan dalam penelitian ini dimaksudkan untuk mendekatkan peneliti dengan masalah yang ada dilapangan sehingga memenuhi prinsip kecukupan dan kepenuhan data yang dibutuhkan. Hasil yang didapatkan, bahwa PAK menempatkan karakteristiknya yang senantiasa berhadapan dengan konteks multikultural, sehingga konteks tersebut bukan untuk dihindari melain-kan dihidupi. Upaya menghidupi konteks multikultural dalam realisasi PAK menempatkan PAK melekat pada dasar kepedulian Yesus yang mengasihi se-tiap orang. Berdasarkan temuan penelitian tersebut, maka sangat disarankan agar senantiasa menempatkan konteks Indonesia menjadi jawaban bagi penca-paian tujuan PAK, budaya Indonesia yang saling menerima, menghormati dan meninggikan prinsip kehidupan bersama.